Endotoxin-Induced Tryptophan Degradation along the Kynurenine Pathway: The Role of Indolamine 2, 3-Dioxygenase and Aryl Hydrocarbon Receptor-Mediated Immunosuppressive Effects in Endotoxin Tolerance and Cancer and Its Implications for Immunoparalysis. (31st December 2015) - Wirthgen, Elisa; Hoeflich, Andreas
Abstract : The degradation of tryptophan (TRP) along the kynurenine pathway plays a crucial role as a neuro- and immunomodulatory mechanism in response to inflammatory stimuli, such as lipopolysaccharides (LPS). In endotoxemia or sepsis, an enhanced activation of the rate-limiting enzyme indoleamine 2, 3-dioxygenase (IDO) is associated with a higher mortality risk. It is assumed that IDO induced immunosuppressive effects provoke the development of a protracted compensatory hypoinflammatory phase up to a complete paralysis of the immune system, which is characterized by an endotoxin tolerance. However, the role of IDO activation in the development of life-threatening immunoparalysis is still poorly understood. Recent reports described the impact of inflammatory IDO activation and aryl hydrocarbon receptor- (AhR-) mediated pathways on the development of LPS tolerance and immune escape of cancer cells. These immunosuppressive mechanisms offer new insights for a better understanding of the development of cellular dysfunctions in immunoparalysis. This review provides a comprehensive update of significant biological functions of TRP metabolites along the kynurenine pathway and the complex regulation of LPS-induced IDO activation. In addition, the review focuses on the role of IDO-AhR-mediated immunosuppressive pathways in endotoxin tolerance and carcinogenesis revealing the significance of enhanced IDO activity for the establishment of life-threatening immunoparalysis in sepsis.